Agency rivalry in a shared regulatory space and its impact on social welfare: The case of aquaculture regulation. Issue 1 (2nd January 2018) - Abate, Tenaw Gedefaw; Nielsen, Rasmus; Nielsen, Max
ABSTRACT: This article is grounded in public choice theory and develops a framework to explain how non-benevolent behavior on the part of public regulators and the resulting lack of collaboration between different agencies have been affecting aquaculture growth. Although regulators are assumed to work for the best interest of the people, they can have their own rational agendas; such as career advancement, self-aggrandizement and loyalty for a particular political ideology. We show that when officials are non-benevolent and agencies have unequal relative decision-making power, it is likely that a more powerful agency dictates policies in favor of its own agenda, even when such policies may not necessarily lead to optimal social welfare. In the case of aquaculture, higher relative power of a pro-environment agency leads to underdevelopment of the sector, as is the case in developed countries, whereas larger relative power of a pro-industry agency leads to higher growth, as is the case in developing countries.